Measurement of azimuthal correlations of D mesons with charged particles in pp collisions at √s=7 TeV and p–Pb collisions at √sNN=5.02 TeV - Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Aiola, S.; Akindinov, A.; Alam, S.N.; et al. (Springer New York LLC, 2017)
The azimuthal correlations of D mesons with charged particles were measured with the ALICE apparatus in pp collisions at √s = 7 TeV and p–Pb collisions at √sNN = 5.02 TeV at the Large Hadron Collider. D0, D+, and D∗+ mesons and their charge conjugates with transverse momentum 3 < pT < 16 GeV/c and rapidity in the nucleonnucleon centre-of-mass system |ycms| < 0.5 (pp collisions) and −0.96 < ycms < 0.04 (p–Pb collisions) were correlated to charged particles with pT > 0.3 GeV/c. The yield of charged particles in the correlation peak induced by the jet containing the D meson and the peak width are compatible within uncertainties in the two collision systems. The data are described within uncertainties by Monte-Carlo simulations based on PYTHIA, POWHEG, and EPOS 3 event generators
Keywords: Physics; Meson; Particle physics; Rapidity; Charged particle; Hadron; Nuclear physics; Nucleon; Ion; https://purl.org/pe-repo/ocde/ford#1.03.04